2021
DOI: 10.3390/s21103378
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Chewing and Swallowing

Abstract: A series of eating behaviors, including chewing and swallowing, is considered to be crucial to the maintenance of good health. However, most such behaviors occur within the human body, and highly invasive methods such as X-rays and fiberscopes must be utilized to collect accurate behavioral data. A simpler method of measurement is needed in healthcare and medical fields; hence, the present study concerns the development of a method to automatically recognize a series of eating behaviors from the sounds produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Early studies mainly focused on the gnathosonic which is related to occlusal stability and interference [ 13 – 16 ]. To date, the related studies have mainly been based on the classification in occlusal sounds of Watt’s work [ 44 , 45 ]. Due to limitations of adapterization and analysis methods, the subsequent doubt centralized the methodology, which lacked meaningful data analysis and complete sound capture [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies mainly focused on the gnathosonic which is related to occlusal stability and interference [ 13 – 16 ]. To date, the related studies have mainly been based on the classification in occlusal sounds of Watt’s work [ 44 , 45 ]. Due to limitations of adapterization and analysis methods, the subsequent doubt centralized the methodology, which lacked meaningful data analysis and complete sound capture [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…During experimentation, it had been found that the Tiny Eats GRU only used 4% of the Arm Cortex M0 + memory and had a lag of 6 ms with a 95.15% accuracy rate when figuring out if an individual was eating or not. Nakamura et al (2021) 17 worked on making an automated way to recognize different items of food based on the sounds made while eating. A combined CTC/attention model was used by the researchers to automatically find left chewing, front biting, right chewing, and swallowing.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, studies have focused on non-invasive and simple methods for evaluating swallowing function, such as evaluation of the tongue, hyoid bone movement, and tongue pressure using ultrasonography, electromyography, and pressure sensors, as well as the assessment of mastication and swallowing using microphones [ 11 , 12 , 13 , 14 ]. All these methods are non-invasive and useful means for obtaining information, but we cannot rule out the possibility that the method of applying an ultrasonic probe to the mandible while swallowing or attaching a sensor to the skin near the oral cavity or larynx may interfere with the movement of various organs involved in swallowing or may cause discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since examination circumstances that vary from routine environments can be the cause of confusion or stress for patients with dementia, it would be ideal for the evaluation of swallowing function to be performed in daily eating/dietary environments [ 16 , 17 ]. Although there have been many studies exploring simple methods to evaluate tongue movement, tongue pressure, and hyoid bone movement [ 11 , 12 , 13 , 14 ], a method that can easily evaluate the soft palate movement, despite its important role in preventing regurgitation of food bolus in the nasal canal while swallowing and generating pressure for the transport of the food bolus, remains to be established [ 18 ].…”
Section: Introductionmentioning
confidence: 99%